Cobalt‐Catalyzed C(sp2)−H Methylation by using Dicumyl Peroxide as both the Methylating Reagent and Hydrogen Acceptor. Issue 35 (30th June 2016) - Li, Qun; Li, Yanrong; Hu, Weipeng; Hu, Renjian; Li, Guigen; Lu, Hongjian
Abstract: The first cobalt‐catalyzed direct methylation of a C(sp 2 )−H bond using dicumyl peroxide (DCP) as both the methylating reagent and hydrogen acceptor has been established. The reaction proceeded without the use of any additives, and was proven to be applicable to various amides bearing a 2‐pyridinylisopropyl (PIP) directing group, providing an efficient access to o ‐methyl aryl amides with high functional‐group tolerance. Preliminary mechanistic studies suggest a radical process would be involved in the catalytic process. Abstract : C−H functionalization : A cobalt‐catalyzed direct methylation of the C(sp 2 )−H bond by using dicumyl peroxide (DCP) as both the methylating reagent and hydrogen acceptor has been established (see scheme; acac=acetylacetone). The reaction proceeded without the use of any additives, and was proven to be applicable to various amides bearing a 2‐pyridinylisopropyl (PIP) directing group.